Metabolic treatment of an electrical disease? Beneficial APD/QT prolongation by L-Carnitine in transgenic SQT1 rabbit models. (14th October 2021) - Hornyik, T; Bodi, I; Michaelides, K; Mettke, L; Perez-Feliz, S; El-Battrawy, I; Brunner, M; Bode, C; Odening, K
Abstract: Background: Short-QT syndrome 1 (SQT1) is a genetic cardiac channelopathy caused by gain-of-function mutations (KCNH2-N588K) in HERG/IKr, that leads to shortened QT-interval, increased risk for arrhythmias and sudden cardiac death (SCD). An acquired form of SQTS has been described in patients with primary (genetic) carnitine-deficiency, indicating that carnitine might affect cardiac repolarization. Purpose: We aimed to investigate potential beneficial (APD/QT-prolonging) effect of L-Carnitine in (genetic) SQTS using transgenic SQT1 rabbits that mimic the human disease phenotype. Methods: Effects of L-carnitine on cardiac repolarisation were assessed in adult wildtype (WT) and transgenic SQT1 rabbits (KCNH2-N588K) using in vivo ECG and ex vivo Langendorff-perfused whole-heart or isolated ventricular cardiomyocyte action potential (AP) recordings. Effects on ion currents were assessed by whole-cell patch-clamping. Results: In vivo, the heart-rate corrected QT index (QTi) was prolonged significantly by L-carnitine both in WT (QTi, baseline 102.7%±4.9 vs. L-carnitine 106.9%±6.2, p<0.05, n=12) and SQT1 (QTi, baseline 94.8%±7.4 vs. L-carnitine 99.5%±8.2, p<0.05, n=13), leading to normalisation of QTi in SQT1. Ex vivo, whole-heart monophasic and cellular APs were also significantly prolonged by L-carnitine in WT and SQT1 (change in monophasic APD75, ms, WT +13.9±4.4, SQT1 +9.9±7.0; change in cellular APD90, %, WT +10.4%, SQT1 +10.4%, all p<0.05). As underlying mechanisms, we identified acute effects on the main repolarizing ion currents IKr and IKs: IKr-steady, which is significantly increased in SQT1 contributing to accelerated repolarization, was reduced by L-carnitine (WT: −23%, SQT1: −16%). Moreover, L-carnitine accelerated the deactivation kinetics of IKr - while no change was observed in IKr-tail. In addition, IKs-steady was decreased by L-carnitine in SQT1 and WT cardiomyocytes. Conclusion: L-carnitine prolongs/normalizes QT and APD in transgenic SQT1 rabbits by decreasing the pathologically increased IKr-steady and also IKs-steady and may therefore serve as potential future anti-arrhythmic therapy in SQTS. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): German Research Foundation (DFG)